2 - Padvinders, Pandu, Pramuka: Youth and State in the 20th Century Indonesia - Semedi, Pujo (Africa Development, 2021)
This article explores the significance of the large and very influential scouting movement in Indonesia, just before and after independence up till the present time. Here again, the emphasis is on the transmission of a very specific set of values and behavioral patterns that not only the scouting movement itself found important, but which became also very much supported by the Indonesian regime. These values entailed a disciplining of youth, a political ensnarement in the preparation of youth for good Indonesian citizenship, an acceptance of the role of the mili- tary as well as a civilization mission that embraced many bourgeois middle class values concerning dress, style, comportment, the body, responsibility and so on. Above all, patriotism was greatly valued; and as such, the scouting movement was capable of taking away much of the critical, if not revolutionary, power that in colonial times was kept by Islamic youth movements opposing colonial authority.